Complications of Laparoscopic and Laparotomy Surgeries in the Department of Tehran Legal Medical Committee in 2011-2016 - Najari, Fares; Mostafazadeh, Babak; Soleimani Natanzi, Leila (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: A major challenge in medicine is patients’ dissatisfaction and complaints against doctors. Medical complaints in Iran, similar to the other countries, have a growing trend. Over the past two decades, the implementation of laparoscopic surgery rapidly grew in many countries. The current study aimed to investigate complaints against surgeons in laparoscopic surgeries, compared to open surgeries. Methods: The current cross-sectional study was conducted on all laparotomy and laparoscopic surgery complaint cases. The medical records were extracted based on the study variables, using a researcher-made questionnaire. To analyze the obtained data, frequency tables were used and to investigate the relationship between variables, Chi-Squared and Fisher’s Exact tests were employed. Results: A total of 369 medical complaint cases were brought to the Department of Tehran Legal Medical Committee, Tehran, Iran, from 2011 to 1016. The Mean±SD age of studied patients was 45.8±13.4 years. The most frequent medical complaint cases were against physicians working at private hospitals. In addition, most complaints were after laparotomy cases. More than half of the cases were voted on the malpractice of physicians. The frequency of postoperative infections was significantly higher in laparoscopic surgeries. The frequency of sentence for malpractice was significantly higher in laparoscopic surgeons, compared to laparotomy ones. Conclusion: Physicians’ knowledge about legal medical issues and building intimate and trustful relationship with patients along with the provision of desirable healthcare services can be effective in reducing medical error complaints.